Critical review of the impact of cover crops on soil properties - Koudahe, Komlan; Allen, Samuel C.; Djaman, Koffi (International Soil and Water Conservation Research, 2022)
Grasses as well as leguminous and non-leguminous broadleaves are the major categories of commonly grown cover crops worldwide. This review focuses on the contribution of cover crops to soil properties. The review first considers the single and mixed cover crops and shows that grass species are desirable for their decay and ability to provide substantial soil cover, broadleaf species are used for their quick decomposition and capacity of releasing residues into the soil, while the leguminous species are used for their ability to fix atmospheric nitrogen. Secondly, the impacts of cover crops on soil health are reviewed. Integrating cover crops into conventional cropping systems may reduce soil bulk density, improve soil structure and hydraulic properties to facilitate increased water infiltration and storage. Crop residue additions from cover crops may enhance soil organic C and N accretion as well as increase availability of P, K, Ca, Fe and Mg in some soil types under certain climatic conditions. Further, cover crops may provide a better condition for microbial activity, abundance, and diversity. Finally, the review shows that through proper management, cover crops may be utilized as an essential component of soil conservation practices for enhanced soil health. Still, further investigation is necessary to determine cover crop effects in additional cropping systems and climatic zones as well as the long-term effects of cover crops on soil properties, subsequent crop yield, and overall cropping system profitability. This review is an important source of information for crop growers, crop management institutions, universities, and crop consultants for sustainable agricultural production.